2017
DOI: 10.1111/apm.12668
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental characteristics and physiology of biofilms in chronic infections of CF patients are strongly affected by the host immune response

Abstract: Jensen PØ, Kolpen M, Kragh KN, K€ uhl M. Microenvironmental characteristics and physiology of biofilms in chronic infections of CF patients are strongly affected by the host immune response. APMIS 2017; 125: 276-288.In vitro studies of Pseudomonas aeruginosa and other pathogenic bacteria in biofilm aggregates have yielded detailed insight into their potential growth modes and metabolic flexibility under exposure to gradients of substrate and electron acceptor. However, the growth pattern of P. aeruginosa in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 158 publications
2
60
0
Order By: Relevance
“…P. aeruginosa is able to grow anaerobically with high biomass yield on NO3 - (Strohm et al, 2007;Line et al, 2014) and further on arginine and pyruvate fermentation (Eschbach et al, 2004;Schreiber et al, 2006) and reduction-oxidation reactions of self-produced phenazines (Price-Whelan et al, 2007). This supports the current setup for studying clinical biofilm where multiple studies have showed that bacterial metabolism is halted by electron acceptor availability (Kragh et al, 2014;Jensen et al, 2017) rather than carbon source.…”
Section: Metabolic Differences Between Single Cells and Biofilmssupporting
confidence: 61%
“…P. aeruginosa is able to grow anaerobically with high biomass yield on NO3 - (Strohm et al, 2007;Line et al, 2014) and further on arginine and pyruvate fermentation (Eschbach et al, 2004;Schreiber et al, 2006) and reduction-oxidation reactions of self-produced phenazines (Price-Whelan et al, 2007). This supports the current setup for studying clinical biofilm where multiple studies have showed that bacterial metabolism is halted by electron acceptor availability (Kragh et al, 2014;Jensen et al, 2017) rather than carbon source.…”
Section: Metabolic Differences Between Single Cells and Biofilmssupporting
confidence: 61%
“…Although its contribution is still poorly understood in the host, anaerobic respiration of P. aeruginosa is likely significant to promote virulence mechanisms in chronic lung infections (13). Indeed, according to O2 assays directly in the lungs of CF patients, the infected endobronchial mucus is subject to severe hypoxia or even anoxia (31).…”
Section: Discussionmentioning
confidence: 99%
“…First, it may be due to the biofilm structure per se may establish an oxygen gradient across. However, this hypothesis is currently questioned due to the strong morphological differences between in vivo and in vitro biofilm production, the last being much more thicker than the first, for example (13). The second hypothesis is that accelerated O2 consumption in the biofilm may result from activated polymorphonuclear leukocytes that produce superoxide (32) and to a lesser extend nitric oxide (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other cells of the host may also consume O 2 , increasing the likelihood of bacteria experiencing anoxia (Worlitzsch et al, 2002). Many chronic infections are thought to contain bacteria in the biofilm mode of growth (Costerton et al, 2003) and endogenous O 2 depletion inside the biofilm (Sønderholm et al, 2018), along with intense O 2 consumption by the host immune response (Worlitzsch et al, 2002;Kolpen et al, 2010;Trunk et al, 2010;Kragh et al, 2014;James et al, 2016;Jensen et al, 2017), may therefore increase the number of VBNC bacteria.…”
Section: Introductionmentioning
confidence: 99%